Clinical Practice Guidance: Surveillance for phaeochromocytoma and paraganglioma in paediatric succinate dehydrogenase gene mutation carriers. (29th January 2019) - Wong, Mei Yin; Andrews, Katrina A.; Challis, Benjamin G.; Park, Soo‐Mi; Acerini, Carlo L.; Maher, Eamonn R.; Casey, Ruth T.
Summary: The succinate dehydrogenase (SDH) enzyme complex functions as a key enzyme coupling the oxidation of succinate to fumarate in the citric acid cycle. Inactivation of this enzyme complex results in the cellular accumulation of the oncometabolite succinate, which is postulated to be a key driver in tumorigenesis. Succinate accumulation inhibits 2‐oxoglutarate‐dependent dioxygenases, including DNA and histone demethylase enzymes and hypoxic gene response regulators. Biallelic inactivation (typically resulting from one inherited and one somatic event) at one of the four genes encoding the SDH complex ( SDHA/B/C/D ) is the most common cause for SDH deficient (dSDH) tumours. Germline mutations in the SDHx genes predispose to a spectrum of tumours including phaeochromocytoma and paraganglioma (PPGL), wild type gastrointestinal stromal tumours (wtGIST) and, less commonly, renal cell carcinoma and pituitary tumours. Furthermore, mutations in the SDHx genes, particularly SDHB, predispose to a higher risk of malignant PPGL, which is associated with a 5‐year mortality of 50%. There is general agreement that biochemical and imaging surveillance should be offered to asymptomatic carriers of SDHx gene mutations in the expectation that this will reduce the morbidity and mortality associated with dSDH tumours. However, there is no consensus on when and how surveillance should be performed in children and young adults. Here, we address the question: "What age should clinical, biochemical and radiological surveillance for PPGL be initiated in paediatric SDHx mutation carriers?".